2020
DOI: 10.1021/acssynbio.0c00009
|View full text |Cite
|
Sign up to set email alerts
|

Cotranscriptional Folding of a Bio-orthogonal Fluorescent Scaffolded RNA Origami

Abstract: The scaffolded origami technique is an attractive tool for engineering nucleic acid nanostructures. This paper demonstrates scaffolded RNA origami folding in vitro in which, for the first time, all components are transcribed simultaneously in a single-pot reaction. Double-stranded DNA sequences are transcribed by T7 RNA polymerase into scaffold and staple strands able to correctly fold in a high synthesis yield into the nanoribbon. Synthesis is successfully confirmed by atomic force microscopy, and the unpurif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…This nuclease resistance can be further increased by modifying the component strands of the structures. 23,24 The ability to produce self-folded RNA origami in vivo 25 and the co-transcriptional folding of an RNA-scaffolded origami structure in vitro 26 make these structure more useful in in vivo applications compared to all-DNA origami structures. The use of RNA in origami nanostructures also opens up the possibility of introducing additional functionalities such as aptamer-based ligand binding to nanostructures, 27 RNA-protein interaction for cargo encapsulation, 28 enzyme-mediated assembly and disassembly, 9 and RNA–RNA kissing interactions for higher order assembly.…”
mentioning
confidence: 99%
“…This nuclease resistance can be further increased by modifying the component strands of the structures. 23,24 The ability to produce self-folded RNA origami in vivo 25 and the co-transcriptional folding of an RNA-scaffolded origami structure in vitro 26 make these structure more useful in in vivo applications compared to all-DNA origami structures. The use of RNA in origami nanostructures also opens up the possibility of introducing additional functionalities such as aptamer-based ligand binding to nanostructures, 27 RNA-protein interaction for cargo encapsulation, 28 enzyme-mediated assembly and disassembly, 9 and RNA–RNA kissing interactions for higher order assembly.…”
mentioning
confidence: 99%
“…RNA origami provides advantages for cellular applications because RNA can be generated via transcription. However, challenges arise because RNA origami designs must consider the isothermal, out-of-equilibrium cotranscriptional folding environments of cells [ 64–67 ], which are starkly different from the controlled annealing environments used for DNA origami. While complex, exciting progress is being made in RNA origami including in vivo folded double and tetra-squares [ 68 ] and Z-tiles that cotranscriptionally fold and oligomerize via intramolecular kissing-loop interactions [ 69 ] ( Figure 2H ).…”
Section: Molecular Scalementioning
confidence: 99%
“…The design also provided multiple potential sites for the coupling of targeting agents in the structure, which is helpful to improve the specificity of RNA delivery. Torelli et al also reported an one-pot strategy for the in vitro construction of RNA origami, in which the RNA scaffolds and staples are co-transcriptionally folded into nanoribbons containing split broccoli aptamers that can be lit up upon binding with specific dye at 37 °C (Torelli et al, 2020). Sugiyamaand coworkers designed and constructed 7-helix bundled planar (7HB-tile) and 6-helix bundled tubular (6HB-tube) RNA origami structures using a 720 nucleotides single-stranded RNA as scaffold (Endo et al, 2014).…”
Section: Application Of Rna Framework In the Construction Of Nanostructuresmentioning
confidence: 99%